Coexistent Crohn's disease and sigmoid diverticulosis. Issue 767 (September 1989) - McCue, J.; Coppen, M. J.; Rasbridge, S. A.; Lock, M. R.
Abstract : This study reports six patients with a diagnosis of diverticular disease with associated localized Crohn's colitis who were all treated by segmental resection. Two patients died in the post-operative period from disease unrelated to their colonic pathology. The remaining four patients remain well, show no signs of recurrent disease and have required no further surgery. The behaviour and significance of the two conditions occurring in the same patient is discussed.